Renal haemodynamic responses to exogenous and endogenous adenosine in conscious dogs - Berthold, Heike; Just, Armin; Kirchheim, Hartmut; Oßwald, Hartmut; Ehmke, Heimo (The journal of physiology, 1998)
1 Adenosine has been suggested to be the mediator of a metabolic feedback mechanism which transfers acute changes in the tubular load into opposite changes in renal blood flow (RBF). The goal of the present experiments was to assess the importance of endogenously formed adenosine as a ‘homeostatic metabolite’ during short-term changes in metabolic demand. 2 In nine chronically instrumented conscious foxhounds, both the direct effects of adenosine injections (10, 30 and 100 nmol) into the renal artery and the temporal changes of RBF after short renal artery occlusions (15, 30 and 60 s duration), the most widely used experimental model to study the metabolic feedback mechanism in vivo, were studied. 3 Intrarenal bolus injections of adenosine (10, 30 and 100 nmol) induced dose-dependent decreases of RBF (RBF: −34 ± 5, −59 ± 4 and −74 ± 4 %, respectively). This vasoconstrictor effect of adenosine was significantly larger (RBF: −51 ± 4, −68 ± 4 and −83 ± 3 %, respectively) when the dogs received a low salt diet. 4 The post-occlusive responses were characterized by a transient hyperaemia with no detectable drop of RBF below the preocclusion level. The post-occlusive responses were affected neither by changes in local angiotensin II levels, nor by intrarenal infusions of hypertonic NaCl or blockade of A1 adenosine receptors. 5 When intrarenal adenosine levels were elevated by infusion of the adenosine uptake inhibitor dipyridamole, a transient, although weak, post-occlusive vasoconstriction was detected. 6 In summary, the present data demonstrate that adenosine acts as a potent renal vasoconstrictor in the conscious dog. The endogenous production of adenosine during short-lasting occlusions of the renal artery, however, appears to be too small to induce a post-occlusive vasoconstrictor response of RBF. These results suggest that a metabolic feedback with adenosine as ‘homeostatic metabolite’ is of minor importance in the short-term regulation of RBF in the conscious, unstressed animal.